The Audit Committee, Sharia Supervisory Board and Audit Report Lag: Empirical study of Islamic Banking - Afra Aziza Hasna; Anis Chariri (Diponegoro Journal of Accounting, 2025)
The purpose of this research is to examine the influence of audit committee and sharia supervisory board on audit report lag. The dependent variable is audit report lag and the independent variables in consist of audit committee size, audit committee expertise, audit committee meetings, sharia supervisory board size, and sharia supervisory board meeting. The population involve Islamic banking companies listed on the Otoritas Jasa Keuangan in 2017 and 2021. The data was analyzed using descriptive statistical analysis and linear regression analysis with the SPSS 25 program. The findings show that, audit committee size and audit committee expertise have a significant relationship with audit report lag. Meanwhile, the audit committee meeting have a negligible relationship with audit report lag. Also, sharia supervisory board size and sharia supervisory board meeting has significant effect on audit report lag.